Classical infratentorial superficial siderosis of the central nervous system: pathophysiology, clinical features and management. Issue 4 (11th July 2022) - Kharytaniuk, Natallia; Cowley, Peter; Sayal, Parag; Eleftheriou, Perla; Farmer, Simon F; Chan, Edgar; Bamiou, Doris-Eva; Werring, David J
Abstract : The term superficial siderosis (SS) is derived from the Greek word 'sideros', meaning iron. It includes two subtypes, distinguished by their anatomical distribution, causes and clinical features: 'classical' infratentorial SS (iSS, which sometimes also affects supratentorial regions) and cortical SS (cSS, which affects only supratentorial regions). This paper considers iSS, a potentially disabling disorder usually associated with very slow persistent or intermittent subarachnoid bleeding from a dural defect, and characterised by progressive hearing and vestibular impairment, ataxia, myelopathy and cognitive dysfunction. The causal dural defect—most often spinal but sometimes in the posterior fossa—typically follows trauma or neurosurgery occurring decades before diagnosis. Increasing recognition of iSS with paramagnetic-sensitive MRI is leading to an unmet clinical need. Given the diagnostic challenges and complex neurological impairments in iSS, we have developed a multidisciplinary approach involving key teams. We discuss pathophysiology, diagnosis and management of iSS, including a proposed clinical care pathway.